Incentivizing Drug Development: Reforms of Pharmaceutical Innovation - Khachatryan, Kevin (Science and Technology Law Review, 2017)
The Food and Drug Administration (“FDA”) has embraced its position as the Gatekeeper of the pharmaceutical industry. However, the agency’s regulatory requirements have stifled innovation in key therapeutic areas. Promoting robust drug development in these “neglected” areas has become a distinct congressional goal. On July 9, 2012, Congress passed the Generating Antibiotic Incentives Now (“GAIN”) Act as part of the Food and Drug Administration Safety and Innovation Act. GAIN increases the exclusivity period of a Qualified Infectious Disease Product (“QIDP”) by five years and provides fast track and priority review by the FDA. The bipartisan legislation responded to the National Strategy on Combating Antibiotic Resistant Bacteria and encouraged the development of drug products to treat serious and life-threatening infections. In 2012, Congress also passed the Rare Pediatric Disease Priority Review Voucher to fight rare pediatric diseases. Several other bills have been proposed to incentivize drug developers — including the groundbreaking 21st Century Cures Act, the Promoting Life-Saving New Therapies for Neonates Act of 2015, and the Advancing Targeted Therapies for Rare Diseases Act of 2015. I begin this article by describing several areas of concern in healthcare and the recent history of congressional reform incentivizing healthcare innovation, including novel legislative-regulatory mechanisms. Then, I describe the newest legislation in detail. I conclude by proposing flexible incentivizing mechanisms that fit neatly into the current regulatory framework.